Ready to Read : Starring Katy Duck - 1957-; Capucilli, Alyssa Satin; Cole, Henry; 1955- (New York, 2011)
Katy Duck is on stage and ready to perform at the dance show, but when the curtain opens, she feels very shy.
"The text of this work is revised from Katy Duck, Center Stage, and the art for this book is taken from Katy Duck, Katy Duck is a Caterpillar, and Katy Duck, Center Stage."
1
Accelerated Reader AR
Keywords: Early readers